2021
DOI: 10.1111/are.15591
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids as chemoattractant and feeding stimulant for the commercially farmed decapod crustaceans: A brief review

Abstract: The aquaculture of decapod crustaceans is expanding continuously to supply protein source for human consumption. Therefore, intensive research is necessary to improve the quality of the feeds in decapod crustacean farming. Decapod crustaceans are slow feeders, and dietary inclusion of plant proteins reduces their intakes on the feeds. Dietary supplementation of chemoattractants (CA) (to reduce food searching duration) and feeding stimulants (FS) (to stimulate ingestion) is therefore necessary to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…Consequently, feed utilization and metabolism enhance, leading to marked growth performance and health status (Dawood, 2021). In addition, betaine can regulate digestive enzymes and result in efficient feed digestion (Lim et al, 2022). Besides, betaine is an attractant agent involved in enhancing the feed intake, which is evident in this study (Adjoumani et al, 2017;Dong et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Consequently, feed utilization and metabolism enhance, leading to marked growth performance and health status (Dawood, 2021). In addition, betaine can regulate digestive enzymes and result in efficient feed digestion (Lim et al, 2022). Besides, betaine is an attractant agent involved in enhancing the feed intake, which is evident in this study (Adjoumani et al, 2017;Dong et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…Betaine is a trimethyl derivative of glycine amino acid and has been extensively applied in the aquafeed industry (Lim et al, 2022). Betaine has many metabolic roles, including osmoregulation and methyl donor (Virtanen et al, 1989).…”
mentioning
confidence: 99%
“…In fish and crustaceans, amino acids in the diet serve not only as the basic unit for protein synthesis 41 but also participate in various functions in the body, including serving as gustatory or olfactory feeding stimulants and catalysis of biological reactions (enzymes). [42][43][44][45] However, when it comes to the determination of the dietary requirement level for a specific EAA, such biochemical or metabolic response criteria are not fully explored, except in a few cases. [46][47][48][49] In our dataset for meta-analysis, all studies recorded fish growth over varying durations during the experiment.…”
Section: Response Criteria and Model Selection For Meta-analysismentioning
confidence: 99%
“…Given that not all aquatic animals are ready to accept formulated diets, several studies on effective chemoattractants and feeding stimulants have been reported. A feeding stimulant triggers an animal to continue feeding once it starts to feed, while the chemoattractant triggers an animal to search and move toward the chemical source ( Lavalli, Spanier & Grasso, 2007 ; Lim et al, 2021 ; Smith et al, 2005 ). Most studies on chemoattraction in crustaceans have demonstrated low molecular weight compounds, including amino acids, amines, nucleotides, and organic acids ( Lee & Meyers, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on chemoattraction in crustaceans have demonstrated low molecular weight compounds, including amino acids, amines, nucleotides, and organic acids ( Lee & Meyers, 1996 ). Amino acids are highly prevalent among these chemoattractants and act as effective attractants that are species-specific in lobsters ( Carter & Steele, 1982 ; Johnson & Ache, 1978 ; Lim et al, 2021 ; Zimmer-Faust, 1987 ; Zimmer-Faust et al, 1984 ).…”
Section: Introductionmentioning
confidence: 99%